Chronological Levels of As, Pd, V, and Sr in 356-year-old Pinus nigra Annual Rings in Northern Türkiye - İsmail Koç (BioResources)
The accumulation and allocation of heavy metals—arsenic (As), strontium (Sr), palladium (Pd), and vanadium (V)—were measured in Pinus nigra wood over more than three centuries. Contrary to expectations, the results did not show a correlation between increasing air pollution in recent decades and the concentrations of these metals in annual rings. Thus, P. nigra wood appears unsuitable as a biomonitor for tracking long-term heavy metal pollution in air. However, metals deposited in specific annual rings remained restricted within those rings, supporting the hypothesis of limited radial migration over time. The study specified P. nigra as a promising candidate for phytoremediation due to its capacity to accumulate high concentrations of As, Sr, Pd, and V. Additionally, these metals exhibited robust positive correlations with other toxic elements (tin, antimony, niobium, silver, thallium, selenium, and lead), suggesting that P. nigra could serve as an indicator of regions with multiple heavy metal pollutants. These findings highlight the complexity of metal uptake and allocation processes in trees and underscore the need for further research in controlled environments to clarify mechanisms of metal transfer and toxicity. Despite its limitations relative to its usage as a biomonitor, P. nigra demonstrated potential for mitigating heavy metal contamination in polluted environments.